The relationship between maximum tolerance and motor activation during transcutaneous spinal stimulation is unaffected by the carrier frequency or vibration. Issue 5 (13th March 2020) - Manson, Gerome A.; Calvert, Jonathan S.; Ling, Jeremiah; Tychhon, Boranai; Ali, Amir; Sayenko, Dimitry G.
Abstract: Transcutaneous spinal stimulation (TSS) is a useful tool to modulate spinal sensorimotor circuits and has emerged as a potential treatment for motor disorders in neurologically impaired populations. One major limitation of TSS is the discomfort associated with high levels of stimulation during the experimental procedure. The objective of this study was to examine if the discomfort caused by TSS can be alleviated using different stimulation paradigms in a neurologically intact population. Tolerance to TSS delivered using conventional biphasic balanced rectangular pulses was compared to two alternative stimulation paradigms: a 5 kHz carrier frequency and biphasic balanced rectangular pulses combined with vibrotactile stimulation. In ten healthy participants, tolerance to TSS was examined using both single‐pulse (0.2 Hz) and continuous (30 Hz) stimulation protocols. In both the single‐pulse and continuous stimulation protocols, participants tolerated significantly higher levels of stimulation with the carrier frequency paradigm compared to the other stimulation paradigms. However, when the maximum tolerable stimulation intensity of each stimulation paradigm was normalized to the intensity required to evoke a lower limb muscle response, there were no statistical differences between the stimulation paradigms. Our results suggest that, when considering the intensity of stimulation required to obtain spinally evoked motor potentials, neither alternative stimulation paradigm is more effective at reducing discomfort than the conventional, unmodulated pulse configuration. Abstract : Studies using transcutaneous spinal stimulation (TSS) have argued that using a burst‐modulated kHz frequency (carrier frequency) to administer spinal stimulation is more optimal because higher stimulation intensities can be tolerated as compared to pulsed stimulation. The present study sought to test whether methods used to reduce discomfort in neuromuscular stimulation are applicable to TSS. To this end, we compared tolerance to TSS administered with pulsed‐current stimulation to two methods found to reduce pain in neuromuscular stimulation: the carrier frequency, and pulsed current stimulation with the addition of local vibration. In sum, the results indicate that there are no differences between the different stimulation paradigms when maximum tolerable intensities are normalized to intensities required to elicit a spinally‐evoked motor potential.